The Effect of Servant Leadership and Compensation on Turnover Intention Through Organizational Commitment - Januar Mansyah; Rojuaniah Rojuaniah (Journal of Multidisciplinary Academic, 2020)
Employees take the most important role in the progress of the community health care center (Puskesmas) organization. Once they get a good work environment, it is more likely to commit to the organization. Its impact is in line with the number for the turnover intention that is lower. This research aimed to determine the effect of servant leadership and compensation on turnover intention through organizational commitment. In this research, we employed the purposive sampling method for data collection techniques with several criteria on the questionnaire. Based on those criteria, it was obtained 200 Puskesmas non-civil servants in West Jakarta, both medical, paramedical, and administrative staff. The data analysis used in this research was the Structural Equation Model (SEM). The results of this research indicated that servant leadership, organizational commitment, and compensation had a direct effect on turnover intention. Servant leadership on one hand affected organizational commitment. On the other hand, compensation explained the indirect effect given to organizational.